Juvenal’s Nabataean grove - Garstad, Benjamin (My University, 2020)
Juvenal speaks of elephants dropping their tusks in a 'Nabataean grove' (Nabataeo … … saltu). The line has troubled commentators, who take the reference to Arabian Nabataea, but note that elephants are not native to Arabia, and largely explain Juvenal mistaking the middleman for the source in the ivory trade. The line is better understood as referring to the city of Napata in Ethiopia, where there were in fact elephants. Pliny and Augustus' Res Gestae confirm that Nabata was an accepted spelling of the Ethiopian city, and the adjective Napataios is attested in Greek at least. Taking the 'Nabataean grove' as near Napata also makes sense of Juvenal's reference in the same passage to the porta Syenes, Syene, a city historically associated with Napata, as the gateway to the African interior. Setting the 'Nabataean grove' in Ethiopia is, moreover, consistent with the mention of elephants elsewhere in Juvenal.
Keywords: Latin literature; Juvenal 11.126; Nabataea; Ethiopia